Pengaruh Kepemimpinan Paternalistik Terhadap Kinerja Pegawai Di Lembaga Penyiaran Publik (LPP) TVRI Stasiun Kalimantan Tengah - Laksminarti Laksminarti; Andika Eko Salustyo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This research aims to know how much influence paternalistic leadership towards employee performance at public broadcaster (LPP) TVRI Central Kalimantan Station. The method used in this research is quantitative, the technique of data collection with Angket (Koesioner), the number of samples in this study was 73 employees/Karyawati at the public broadcaster TVRI Central Kalimantan station. Sampling techniques are Total samples. To obtain data on the variables relating to the influence of paternalistic leadership towards personnel performance at public broadcaster (LPP) TVRI Central Kalimantan Satasiun used measuring instruments using statistical method is Using a simple linear regression analysis calculation technique. The results of paternalistic leadership influence rarely give opportunities to subordinates to work influence on employee performance including quality of work, the quantity of work, discipline, and cooperation between employees Public Broadcasting Agency (LPP) TVRI Central Kalimantan Station.